PENGARUH KOMUNIKASI PEMASARAN DANCITRA MEREK SERTA KUALITAS PRODUK TERHADAP KEPERCAYAAN DALAM KEPUTUSAN PEMBELIAN SEMEN PUGER DI KOTA SEMARANG - Ami Nurhayati (Jurnal Riset Bisnis Indonesia, 2014)
The purposes of this research are 1) to describe and analyze the effect of marketing communications,branding image and product quality on consumer trust, 2) to describe and analyze the effect of truston the purchasing decision. The population in this research is Puger Cement consumers residing inSemarang. The number of sample is 67 people who were selected using non-probability method, thatis purposive sampling method. The data in this research is primary data obtained from questionnairesand distributed to respondents. Data were analyzed using Partial Least Square (PLS). Based on theresults of research and study, it can be concluded that 1) marketing communications positively andsignificantly effect on trust, 2) branding image positively and significantly effect on trust, 3) quality ofthe product positively and significantly effect on trust, 4) marketing communications positively andsignificantly effect on purchasing decisions, 5) branding image does not positively and significantlyeffect on purchasing decision, 6) quality of the product does not positively and significantly effect onpurchasing decision, 7) trust positively and significantly effect on purchasing decisions.Keywords: Marketing communications, branding image, product quality, trust, purchasing decision.